2011
DOI: 10.1016/j.vetpar.2011.04.040
|View full text |Cite
|
Sign up to set email alerts
|

An intestinal Eimeria infection in juvenile Asian seabass (Lates calcarifer) cultured in Vietnam – A first report

Abstract: An intestinal Eimeria infection in juvenile Asian seabass (Lates calcarifer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…infection in Malaysia was first published by Boulard (1977) In a study on parasites of specimens of L. calcarifer cultured in Malaysian cage cultures we also found coccidian oöcysts in the intestine of this species which we were able to examine from fresh material. The structure of the oöcysts of this coccidium corresponded to that reported earlier by Gibson-Kueh et al (2011a, b). Sporulated oöcysts of this species bear the typical signs of the genus Goussia Labbé, 1986.…”
Section: Among Infectious Diseases Viral Nervous Necrosis and A Bactsupporting
confidence: 86%
See 4 more Smart Citations
“…infection in Malaysia was first published by Boulard (1977) In a study on parasites of specimens of L. calcarifer cultured in Malaysian cage cultures we also found coccidian oöcysts in the intestine of this species which we were able to examine from fresh material. The structure of the oöcysts of this coccidium corresponded to that reported earlier by Gibson-Kueh et al (2011a, b). Sporulated oöcysts of this species bear the typical signs of the genus Goussia Labbé, 1986.…”
Section: Among Infectious Diseases Viral Nervous Necrosis and A Bactsupporting
confidence: 86%
“…Although no developing stages were found in the histological sections and SEM preparations made from an advanced stage of development, the morphological identity of the oöcysts presented by Gibson-Kueh et al (2011a) from fixed material and the oöcysts found by us in the fresh intestinal mucus, proves that the two cases represent a single coccidian species of the epicellular type, described here as G. kuehae n. sp. The stages found by Gibson-Kueh et al (2011a) in the intestine of the Asian seabass in Vietnam, Australia and Malaysia were located epicellularly in the intestinal epithelium and thus resembled G. pannonica Molnár, 1989 and G. janae Lukeš & Dykova, 1990(see Molnár, 1989Lukeš & Dykova, 1990).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations